CIAT Institutional Video - International Center for Tropical Agriculture (2012)
CIAT is an international agricultural research organization focused on eco-efficient agriculture, that is, farming systems that better harness the available resources to be more competitive and to sustainably increase productivity, while leaving a smaller environmental footprint.